Vermicompost Enriched with Organic Additives for Sustainable Soil Health - Sheeba P S (Department of Soil Science and Agricultural Chemistry College of Agriculture, 2004)
An investigation was carried out at the Instructional Farm, attached to the College of Agriculture, Vellayani to evaluate the effect of vermicompost enriched with organic additives viz., neem cake and bone meal on physico-chemical and biological properties of soil, to evaluate its impact on crop performance and the feasibility of substituting farmyard manure and inorganic fertilizer using amaranthus as test crop. The study consist of three parts 1) Preparation and analysis of vermicompost and enriched vermicompost 2) laboratory incubation experiment 3) Field experiment. On enriching biowastes with neem cake and bone meal, improved the manurial value of vermicompost produced using earthworm species Eudrillus eugeniae. C/N ratio was reduced by enrichment. Microbial population also increased considerably by enriching vermicompost with organic additives. Second part of our investigation was an incubation study and it was conducted to evaluate relative efficiency of enriched vermicompost to release nutrients from soil and its influence on physico-chemical and biological properties of soil. The results revealed that available nitrogen, phosphorus and potassium content of the soil increased upto 45 days of incubation then the availability slowly declined. Organic carbon, pH and EC increased whereas bulk density reduced due to the effects of various organic sources. Application of organic matter had a positive effect on microbial count also. Third part of the study was field experiment, and it was laid out in RBD with 10 treatments and three replications. The biometric observations viz., plant height, number of leaves, number of branches, stem girth, leaf stem ratio all were significantly influenced by different treatments. Significant differences were observed among yield attributing characters like yield per cutting (t ha-1), total yield per plant (g plant-1), total marketable yield (t ha-1), and total dry matter production (t ha-1). Highest yield per cutting was recorded by the treatments T0 (FYM + full NPK), T4 (EVC – NC two per cent + full NPK) and T8 (EVC – NC 1 per cent + BM 1 per cent + full NPK]. With respect to plant contents of nutrients, for nitrogen, highest value was recorded by the treatment T4 (EVC – NC two per cent + full NPK), for P, highest value was recorded by T6 (EVC – BM two per cent + full NPK) and for K, highest value was recorded by the treatment T8 (EVC – NC 1 per cent + BM 1 per cent + full NPK). For plant uptake highest values were registered by the treatments T4, T6 and T8 for N, P and K respectively. With respect to quality characters, treatments with organic sources of plant nutrients viz., T8 [EVC- NC 1 per cent + BM 1 per cent + full NPK) recorded highest value for -carotene content in all the three cuttings, for moisture content T3 (VC+1/2NPK) recorded the highest value in all cuttings, for protein T4 (EVC – NC two per cent + full NPK) recorded the highest value in all cuttings. For fibre content treatment T1(Full NPK as mineral fertilizer) recorded the highest value and T2 (VC + full NPK) recorded the lowest value. Oxalate content is also influenced by different treatments. Vermicompost enriched with bone meal and treatment received NPK alone recorded highest oxalate content. Post harvest analysis of the soil indicated that organic carbon, available phosphorus, pH, EC and microbial count were increased by applying enriched vermicompost. But available nitrogen and available potassium were slightly decreased. Bulk density was found to be influenced favourably. From the investigation it was proved that enriched vermicompost established its superiority over other organic sources and POP recommendation with respect to soil health and quality of amaranthus. Study also revealed the feasibility of substituting FYM and inorganic fertilizer with enriched vermicompost.